Dramatized discourse : the Mandarin Chinese ba-construction - Jing-Schmidt, Zhuo (Studies in functional and structural linguistics ;, 2005)
Language is a symbolic system of meanings evoked by linguistic forms. The choice of forms in communication is non-arbitrary. Rather, speakers pick those forms whose meanings best convey their discourse intention. The meaning of the Mandarin ba-construction, argues Jing-Schmidt, is discourse dramaticity, a concept that includes high conceptual salience and subjectivity. The ba-construction and its "syntactic variations" are never interchangeable because contrast in their meanings determines difference in their functions. Quantitative analyses based on authentic data validate the postulation of